Design of a Web-Based Campus Asset Management Information System - Febryan Hari Purwanto; Alfarisi, Firmansyah (SMART : Jurnal Teknologi Informasi dan Komputer, 2024)
Campus assets are essential resources that support academic, research, and operational activities in higher education institutions. Effective asset management is necessary to ensure optimal resource utilization. However, many institutions still rely on traditional methods, such as manual recording with spreadsheets, which can lead to data inaccuracies, document loss, and difficulties in asset tracking. Therefore, this study aims to design and develop a web-based Campus Asset Management Information System to enhance asset management efficiency. The research methodology includes interviews with users and asset managers, observations of the current system, and a literature review on asset management information systems. The result of this study is a web-based system that enables faster and more accurate asset recording, speeds up report generation, and facilitates real-time asset tracking and verification. The system is developed using PHP programming language with a MySQL database and is implemented on a server with a static public IP, allowing access from various locations. With this system, campus asset management becomes more structured, transparent, and accountable, improving the efficiency and effectiveness of asset recording and monitoring.